Implementasi Metode User Centered Design (UCD) dengan Framework Kanban dalam Membangun Desain Interaksi - Rudi Hartono; Teguh Ikhlas Ramadhan (Jurnal Algoritma, 2022)
Interaction design is now widespread in product and service development. Various software developers are competing to create applications that can provide a pleasant experience for their users. This has an impact on user loyalty in using an application which is a challenge for developers to continuously improve quality and provide user experience so that it can be easily and easily understood how the flow of the application flows properly. The purpose of this research is how to apply the User Centered Design (UCD) method with the Kanban framework in designing an interaction design that suits user needs so that users can easily understand and use the application. In achieving the objectives of the research, the User-Centered Design (UCD) method was applied where this method focuses on a design by directly involving users in system development activities. In addition, a framework was created using a kanban as a monitoring process during the research. The conclusion of this study is that the application of interaction design using the UCD method and the Kanban framework can create an easy-to-use interaction design.